Propuesta de un plan de comunicación estratégica y relaciones públicas orientado a recuperar el interés de los actuales miembros de la Fundación Ecuatoriana de Esclerosis Múltiple, sede Quito, y captar mayores recursos económicos para que la Fundación pueda cumplir exitosamente su labor - Moncayo del Pozo, María Gabriela (2013)
This thesis work was developed with the aim to propose communication strategies that enable the Ecuadorian Foundation for Multiple Sclerosis (FUNDEM) to obtain the resources needed to achieve their goals, which is why the solutions to possible conflicts were collected through responses obtained from the research. The main focus of this research was to find the links of target audiences with the Foundation, to thereby empower stakeholders in FUNDEM plans. This Strategic Communications and Public Relations Plan is focused on finding the points at which all the interested parties put their efforts to create dialogues that promote the interest of the audience. Working without a budget encourages the creativity of the Corporate Communicator so he employs new strategies and innovative tactics to lower cost. So the results begin to show communication as an investment rather than as an expense. At the end of this Undergraduate Degree Work it is easy to observe the influence that programmed communication activities can have based on the achievement of the strategic objectives of an organization.